How Tough Are Pencak Silat Student Athletes in the Face of Burnout - Mardiana, Lisna; Sofia, Lisda; Ramadhani, Ayunda (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Student athlete in a dormitory is certainly a challenge because they are must to balance academic achievements and non-academic. These all challenges and demands become stressors that lead to burnout in pencak silat athletes, for that hardiness is needed to overcome the burnout. The purpose of this study is to see how hardiness describes pencak silat athletes who experience burnout. The subjects of this study were pencak silat athletes from SKOI East Kalimantan experiencing burnout. In data collection methods, researchers used in-depth interviews and observation data collection techniques. The toughness possessed by student pencak silat athletes is illustrated by their responsibility to complete a heavy training program, being able to overcome pressure in competing, viewing defeat as an opportunity to develop, being able to follow the rules and regulations in SKOI East Kalimantan. This is driven by the mastery of experience as a student martial arts athlete and the support of parents. This research can be used as evaluation for development of student martial arts athletes, especially those in the dormitory.Atlet pelajar yang berada di asrama tentu memiliki tantangan tersendiri karena dituntut untuk dapat menyeimbangkan prestasi akademik dan non akademik. Tantangan ini seringkali menjadi stresor yang mengakibatkan terjadinya burnout pada atlet pencak silat, untuk itu dibutuhkan ketangguhan untuk mengatasi burnout. Penelitian ini dilakukan untuk melihat bagaimana gambaran ketangguhan pada atlet pencak silat yang mengalami burnout. Subjek penelitian ini adalah atlet pencak silat SKOI Kaltim yang mengalami burnout. Pada metode pengambilan data, peneliti menggunakan teknik pengambilan data wawancara mendalam dan observasi. Ketangguhan yang dimiliki oleh atlet pencak silat pelajar digambarkan dengan adanya tanggung jawab untuk menyelesaikan program berat latihan, mampu mengatasi tekanan dalam bertanding, memandang kekalahan sebagai peluang untuk berkembang, mampu mengikuti aturan dan ketentuan yang ada di SKOI Kaltim. Hal ini didorong oleh adanya penguasaan pengalaman sebagai atlet pencak silat pelajar dan adanya dukungan dari orang tua. Penelitian ini dapat dijadikan sebagai bahan evaluasi bagi pengembangan atlet pencak silat pelajar khususnya yang berada di asrama.